Avoid Fraud During Emergencies - Mary Harrison (EDIS)
When there is an emergency situation most people strive to be helpful to others. But, there are a few individuals who will take advantage of the situation and use it for personal gain by victimizing others. This document is FCS9193, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611: First published: May 2003.